Factors affecting the revenue of auctioneers in one Thai pay-to-bid website - Tartat Mokkhamakkul; Chatpong Tangmanee (Global Business & Finance Review (GBFR), 2022)
Purpose: The purpose of this study is to examine whether the six independent factors (i.e., the item retail price, the number of bidders, the bidding duration, the shipping cost, the bidder option and the fee return option) could significantly explain the revenue of the auctioneers in one pay-to-bid (PTB) website. Design/methodology/approach: The data were collected using a python script that crawled into one PTB website in Thailand. They were gathered in two steps. First, the script collected the bidding-level data. Among them were the transaction number, the time at which the bid was placed, the bidding price, and the other identifications that allowed us to keep track of all bidding transactions. These details further helped to create the auction-level data on which the main analyses were performed. Findings: Based on the regression analytic results, all independent variables except the shipping cost significantly explained the PTB auctioneers' revenue. The other statistics confirmed the quality of the findings. The retail price of the bid item and the bidding duration have the most significant explanatory effects on the revenue for their highest Beta values. Research limitations/implications: The findings offer practical implications, one of which is based on the significance of the bidder and the fee return options. PTB auctioneers should offer non-winning bidders the compensation for the sunk cost of the paid bidding fees. One limitation in this study is that the retail value of the bid item is overpriced. Fellow researchers may therefore calibrate it with the similar information from other credible sources before performing the analysis. Originality/value: The study's unique contribution is the empirical validation in which the bidder and the fee return options are significant factors in explaining the PTB owner's revenue. This is in addition to the success in extending theoretical insights into research inspecting factors affecting the revenue in the Thai context.
Keywords: 650; Auctioneers; Revenue; Affecting Factors; Pay-to-Bid Website